Ectopic Cushing’s Syndrome as the Initial Presentation of Pulmonary Carcinoid Tumor Managed by Etomidate: A Case Report - Masoud Mohebbi; Shohreh Vojouhi; Seyed Alireza Javadinia; Faeze Keihanian; Mohammad Ali Yaghoubi; Ali Motamedzadeh Torghabeh (Acta Medica Iranica, 2020)
Ectopic increase of adrenocorticotropic hormone (ACTH) or ectopic Cushing syndrome is a rare initial presentation of small cell carcinoma and carcinoid tumor of the lung. Here, we reported a 36-year-old male with atypical symptoms of Cushing syndrome managed by Etomidate that had a central pulmonary nodule, and pathologic evaluation of pulmonary lobectomy revealed the diagnosis of well-differentiated, low-grade typical carcinoids of lung.